STUDI ADAPTASI SAMAMA (Anthocephalus macrophyllus) PADA BERBAGAI KONSENTRASI TIMBAL (Pb) - Bayu Winata; Basuki Wasis; Yadi Setiadi (Graduate School Bogor Agricultural University (SPs IPB), 2016)
Tailing from the mining activity contains heavy metals such as lead. Heavy metal can causing negative effects to organism and to environmental. Phytoremediation is a method that applied to remove harmful pollutant such as lead by using plant. Information about trees species that has ability to grow and accumulate the Pb is still very less. Anthocephalus macrophyllus (samama) is a pioneer, fast growing trees species, and mostly used for revegetation on postmining land. The aims of this study were to analyze the effect of Pb increment to the growth and adaptability of samama seedling to accumulate Pb. The results showed that Pb effected on plants growth and adaptability. Samama showed good growth and adaptability on increment of 900 mg Pb/kg tailingwith a high tolerance index (TI > 100%).Samama produced 20.65 g biomass with total Pb accumulation was 359.88 mg/kg. Samamahad a good potencial adaptability.